(untitled) (Orfeu, 2017)
This article proposes an interpretative reflection on the Piano Prelude n.1 by Eunice Katunda, the sole piece that was transcripted, from a collection of thirty Preludes which were recorded on tape by the composer herself. It aims to raise interpretative hypothesis around the observation written down in the score by the composer herself, “à maneira popular”, “in a folkway’.